Association and Prognostic Implication of C-Reactive Protein with Risk of 1-Year Death or Disabling Stroke After Transcatheter Aortic Valve Replacement. Issue 4 (4th July 2019) - Do, Ungjeong; Ahn, Jung-Min; Kang, Do-Yoon; Ko, Euihong; Kim, Ho Jin; Kim, Joon Bum; Choo, Suk Jung; Park, Duk-Woo; Park, Seung-Jung
ABSTRACT: Background : Recent data suggest that serum biomarkers may predict worse outcomes in patients undergoing transcatheter aortic valve replacement (TAVR). We examined the association and predictive value of preprocedural levels of C-reactive protein (CRP) with clinical outcomes after TAVR. Methods : We evaluated 243 patients who had undergone successful TAVR and had a valid measurement of baseline CRP level between March 2010 and February 2017. The primary endpoint was the composite of death from any cause or disabling stroke at 12 months. Results : During follow-up (median, 13.7 months), primary outcome events occurred in 18 patients (8.2%), including 14 deaths (6.7%) and 5 disabling strokes (2.1%). Patients with high serum levels of CRP (≥3.0 mg/L) had a significantly higher 1-year rate of death or disabling stroke compared to those with normal CRP levels (16.7% vs. 5.5%, P = 0.009). In the multivariate Cox-proportional hazard model, an elevated level of CRP was identified as an independent predictor of 1-year death or disabling stroke (hazard ratio, 2.84; 95% confidence interval, 1.10–7.34; P = 0.03). After the addition of information about CRP concentration to the Society of Thoracic Surgeons (STS) score model, the C-index for the prediction of death or disabling stroke substantially increased from 0.655 to 0.710, and a continuous net reclassification improvement of 0.529 (0.054–1.004) was noted. And there was no significant relationship between the primary outcome and other biomarkers, included B-type natriuretic peptide (BNP) and troponin I, in our study. Conclusions : In patients undergoing TAVR, elevated CRP levels were significantly associated with an increased risk of death or disabling stroke and also augmented event prediction, suggesting that CRP could be used as biomarker into a risk prediction model for TAVR.